Lung Cancer Brain Metastases. Issue 5 (September 2015) - Goldberg, Sarah B.; Contessa, Joseph N.; Omay, Sacit B.; Chiang, Veronica
<x xml:space="preserve">Abstract</x> Abstract Brain metastases are common among patients with lung cancer and have been associated with significant morbidity and limited survival. However, the treatment of brain metastases has evolved as the field has advanced in terms of central nervous system imaging, surgical technique, and radiotherapy technology. This has allowed patients to receive improved treatment with less toxicity and more durable benefit. In addition, there have been significant advances in systemic therapy for lung cancer in recent years, and several treatments including chemotherapy, targeted therapy, and immunotherapy exhibit activity in the central nervous system. Utilizing systemic therapy for treating brain metastases can avoid or delay local therapy and often allows patients to receive effective treatment for both intracranial and extracranial disease. Determining the appropriate treatment for patients with lung cancer brain metastases therefore requires a clear understanding of intracranial disease burden, tumor histology, molecular characteristics, and overall cancer prognosis. This review provides updates on the current state of surgery and radiotherapy for the treatment of brain metastases, as well as an overview of systemic therapy options that may be effective in select patients with intracranial metastases from lung cancer.